Faktor-Faktor yang Mempengaruhi Inovasi dalam Sektor Penerbangan: Kapabilitas Sumber Daya Manusia, Kemajuan Teknologi, dan Prominensi Energi Bersih - Supardam, Dhian; Raza Bunahri, Rifqi (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The significant changes in the international stage have raised new challenges for the aviation world. In order to cope with these challenges, the aviaton sector has been encouraged to apply innovation, both in its products and services. This article then aims to explain some factors that are influencing innovation in the aviation sector. The method used in this article is qualitative research method by focusing on the literature review. Therefore, the authors are focusing to analyze the secondary data to gain answers to research’s problems. The result shows that there are three factors influencing innovation in the aviation sector, namely human resource capability, technology advancement, and clear energy prominence. These three factors have a positive influence, so they can encourage the aviation sector to keep innovating.